(untitled) - Lewis, Ricki (Boston, 2008)
Explains what genes are, how they function, how they interact with the environment, and how our understanding of genetics has changed since completion of the human genome project. This book is intended for citizens who will be responsible for evaluating new medical options, new foods, and new technologies in the age of genomics.
Keywords: Human genetics,Di truyền học con người